The Nominee: A Political and Spiritual Journey - LESLIE H. SOUTHWICK (University Press of Mississippi, 2013)
In January 2007, I was nominated by President George W. Bush to a seat on the United States Court of Appeals for the Fifth Circuit from Mississippi. In early May, and continuing for almost six months, I became in news reports and opposing senatorsâ€™ speeches and too many other places â€œthe controversial judicial nominee.â€ That phrase represented the essence of who I was to people newly aware of me, in the way that others who for a brief time appear repeatedly in the news are given memorable short descriptions preceding their names as a reminder to the reader, such as â€œgold-medal gymnast,â€ or â€œshark-attack victim,â€ or â€œsuspected drive-by shooter.â€ My struggle for confirmation was not in the category of a trial in which a finding of guilt or innocence would lead to incarceration or freedom. My honor was under siege, my ambitions might have been thwarted, but defeat in the battle thrust unhappily upon me would have left me standing, not abandoned by family and friends, and able to continue my profession. I discuss difficulties, but I am aware that many people have faced far worse. When I write about misery, or being discouraged, or feeling unfairly treated, the context should be remembered. The comforts of life teach little, as enjoyable as they are. My confirmation trials got me the closest I have ever been to a sense of what it means to have a â€œdark night of the soul.â€ That is a phrase used by a sixteenth-century Spanish priest now known as Saint John of the Cross, who was referring to a spiritual crisis that can lead to the necessary full acceptance of our need for God. The ten months of the experience were lived in a furnace of criticism, leading to a sense of being wronged, to occasional anger, and to constant uncertainties. I was broken down, opened up, and, by grace, allowed a better understanding of my motivations and temptations and therefore those of others. With the individuals who most bitterly opposed me, I share a flawed humanity.